Risk Assessment Of Aflatoxins In Nuts And Nut Products Amongst Adult Population In The State Of Pulau Pinang - Leong, Yin Hui (2011)
Aflatoxins have been identified the most serious threat to public health among the known mycotoxins, due to their highly toxic and carcinogenic effect in human and animals. In this study, risk assessment of aflatoxins in nuts and nut products amongst adult population in Pulau Pinang State was conducted. This study involved collecting data on nuts (groundnuts, tree nuts and their products) consumption by selected respondents from five districts of Pulau Pinang, analysis of contamination levels of aflatoxins in nuts, and estimation of risk on aflatoxins exposure using the margin of exposure (MOE) approach.